Bhangra boogie - Khan, Hena (Quill Tree Books, an imprint of HarperCollinsPublishers, 2025)
"Talia wants to be as graceful as the bhangra dancers at the mehndi: Bend! Twirl! Snap! But her feet drag and her arms freeze when she tries to dance in front of others. Instead, she shrinks in her chair. But maybe with some help from her dadi, Talia will find the courage to take to the floor. Then, can she convince Dadi to join her?"--